Implikasi Kuliah Kerja Nyata (KKN) dalam Mendidik Generasi Qurani di Masa Pandemi Covid-19 - Sri Lestari; Nini Ardian; Nursapia Harahap (Universitas Muhammadiyah Enrekang, 2021)
Real Work Lectures (KKN) are a forum for the application and development of science and technology, which are carried out outside the campus within certain time, work mechanisms, and requirements. During this Covid-19 pandemic, we are expected to be motivators and facilitators of development efforts and even education, especially in rural area. The community can share existing problems and find solutions with the participation of KKN participants, cooperation is established in the education process to create a Qur'ani generation. The goals expected in this activity are: a) Kota Tengah village children have the ability and understanding of the Koran; b) more deeply in the sciences of tajwid and makhraj in learning the Koran; c) Knowing the laws of reading in the Koran so as to minimize errors in reading. The method used in the implementation of KKN is the PAR method. This method is an action research activity as a result of the research process, namely research that begins with planning, carrying out an action or action, and evaluating the results of the action. The research process is an act of understanding and changing social practice and involving practitioners in the stages of research. Some of the results that will be achieved in this KKN activity are the creation of Qurani generation children who understand the laws of reading, recitation, and makhraj in the Koran in Kota Tengah Village.